An elderly male with tubercular osteomyelitis of the chest wall. (8th March 2011) - Koul, Parvaiz A; Ashraf, M; Jan, Rafi A; Shah, SU; Khan, Umar H; Ahmad, Feroze; Qadri, Baseer A; Bazaz, Sajjad R
Abstract : Primary tuberculosis of the ribs is rare. A 70-year-old male presented with a 6-month history of a chest wall swelling that ruptured over few weeks to lead to a chronic discharging sinus. He had been administered multiple antibiotics, but the discharge continued. Clinical examination revealed anaemia, cervical lymphadenopathy and a 2-cm splenomegaly. Investigations revealed a normochromic and normocytic anaemia (Hb 7.0 g/dl), an ESR of 60 and a positive tuberculin sensitivity test of 25 mm. Surgical excision of the sinus along with the underlying revealed a caseous rib with histopathological features of a caseating granuloma. The patient was put on antitubercular therapy and is doing well on follow-up.